Peningkatan Produktivitas Usaha Melalui Pemahaman Kewirausahaan, Pelatihan Kewirausahaan dan Minat Berwirausaha - Sukirman Sukirman; Afifi Zaenal (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
The purpose of this study is to analyze the effect of understanding entrepreneurship and entrepreneurship training on interest in entrepreneurship, the effect of understanding entrepreneurship and entrepreneurship training on business productivity and the effect of interest in entrepreneurship on business productivity. The population in this study were 264 students participating in the entrepreneurship development program at Muria Kudus University. Determination of the number of samples using the Slovin formula consists of 136 students, with a side technique using proportional random sampling. Data analysis techniques using Structural Equation Modeling (SEM) with AMOS 21 software. The results showed that understanding of entrepreneurship and entrepreneurship training had a positive and significant effect on interest in entrepreneurship, understanding of entrepreneurship and entrepreneurship training had a positive and significant effect on business productivity and interest in entrepreneurship had a positive and significant effect on business productivity. interest in entrepreneurship has a positive and significant influence in mediating the understanding of entrepreneurship on business productivity. Interest in entrepreneurship has a positive influence to become an intervening in mediating entrepreneurship training on business productivity